#2**+5 **

\(Tangent = \frac{Opposite}{Adjacent}\)

Since we already have the opposite, we need to solve for the adjacent.

Pythagoras: \(a^2 + b^2 = c^2\)

In this case: \(Opposite^2+Adjacent^2=Hypotenuse^2\)

Solve for adjacent:

\(Adjacent^2=Hypotenuse^2-Opposite^2\)

\(Adjacent = \sqrt{Hypotenuse^2-Opposite^2}\)

So, going back to the first equation (for tangent), we can plug in this for adjacent.

\(Tangent=\frac{Opposite}{\sqrt{Hypotenuse^2-Opposite^2}}\)

There we go! Use this equation ↑↑↑ to find tangent.

Guest Mar 9, 2017

edited by
Guest
Mar 9, 2017